(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A hospital management system (HMS) is a web-based platform solution that helps healthcare providers manage daily operations more efficiently. It typically includes modules for patient registration, appointment scheduling, medical records, inventory, supply, and billing and includes subsystem logistics management, human resources, core management, and finance. Hospital management logistics also involves managing the transportation of patients, medical supplies, and equipment. This includes managing the vehicle and ambulance services, organizing patient transfers, and coordinating the delivery of medical supplies and equipment to other healthcare facilities. Hospital Management Logistics Two is about managing resources efficiently and can help automate many of these tasks, making it easier to manage supply, equipment maintenance, and patient transportation; hospital management logistics 2 eliminates the possible harm in transactions, such as validating requests and other department request, to avoid the consumption risk of an anonymous person. Lack of transaction monitoring, mistaken auditing of payment receipts, product information, and document information. As a result, the Project team has eliminated the issues. Validating requests: the project team develops a request form to validate requests with the help of gathering their information. This technique can avoid the consumption risk of an anonymous person. Transaction Monitoring: The project team developed a portal to improve and ensure a smooth flow of products and services between suppliers, vendors, and other management. Auditing payment receipts: The project team developed payment receivables for their vendor and other management that are connected to logistics and management. Provided document information: the project team developed tracking that can track where the documents are delivered to ensure that the correct goods are shipped, received, and billed. Our study encourages resolutions to make it easier to use. Hospital management logistics 2: effectively managing the supply of products and delivering them to the management. Hospital management logistics two can enhance visibility by implementing technology, adopting automation, and collaborating with stakeholders. Hospital management Logistics two also improves transaction and functionalities of the system by integrating subsystems in the hospital management system, which provides some future that can post some requests for finding vendors and posting assets for the hospital, transact supply products, have visibility into shipping and receiving processes, and track shipments, payment transactions, and documents for items.